2020
DOI: 10.1101/2020.10.27.358374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Suppressing STAT3 activity protects the endothelial barrier from VEGF-mediated vascular permeability

Abstract: Vascular permeability can be triggered by inflammation or ischemia in the heart, brain, or lung, where it promotes edema, exacerbates disease progression, and impairs tissue recovery. Vascular endothelial growth factor (VEGF) is a potent inducer of vascular permeability, and VEGF plays an integral role in regulating vascular barrier function in physiological conditions and a variety of pathologies, such as cancer, ischemic stroke, cardiovascular disease, retinal conditions, and COVID-19-associated pulmonary ed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 85 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…The mechanism of transient leukocytopenia soon after combination therapy is unknown; however, considering that leukocytopenia occurred in a very short period, the temporally abnormal distribution of leukocytes may be a potential cause. Indeed, inhibition of signal transducer and activator of transcription 3 (STAT3) phosphorylation reduces intracellular adhesion molecule 1 (ICAM1) expression [ 4 ], which may inhibit the adhesion of neutrophils to blood vessel walls and facilitate extravascular migration. Given that baricitinib is a reversible inhibitor of Janus kinase (JAK) 1/JAK2, which suppresses cytokine-induced phosphorylation of STAT3, baricitinib potentially induces short-term leukocyte depletion in blood, and thus, transient leukocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of transient leukocytopenia soon after combination therapy is unknown; however, considering that leukocytopenia occurred in a very short period, the temporally abnormal distribution of leukocytes may be a potential cause. Indeed, inhibition of signal transducer and activator of transcription 3 (STAT3) phosphorylation reduces intracellular adhesion molecule 1 (ICAM1) expression [ 4 ], which may inhibit the adhesion of neutrophils to blood vessel walls and facilitate extravascular migration. Given that baricitinib is a reversible inhibitor of Janus kinase (JAK) 1/JAK2, which suppresses cytokine-induced phosphorylation of STAT3, baricitinib potentially induces short-term leukocyte depletion in blood, and thus, transient leukocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF has important pro-angiogenic activity and participates in the regulation of normal and pathological angiogenesis (Melincovici et al, 2018). VEGF can induce leakage of blood vessels, and its increased expression can promote vascular hyperpermeability, edema and tissue damage (Wang et al, 2020). In sepsis, VEGF leads to vascular leakage and enhanced host response (Schuetz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the pathway analysis, we found that laminarin's targets played a role in many cell signaling pathways related to COVID-19 and cervical carcinoma. The VEGF signaling pathway plays a vital role in the pathologies of COVID-19-associated pulmonary edema, sepsis, and acute lung injury (Wang et al, 2021). A clinical comparison study among the COVID-19 patient categories found a significantly lower level of VEGF in the mildly symptomatic patients (Tripathy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%